An Analysis of Students' Problems of Speaking English in Grade VIII of SMPN 3 Sungai Limau - Yolla Syahdila; Edi Trisno (Universitas Negeri Padang, 2023)
This study aims to know the students’ problems of speaking English and the dominant problems faced by students at grade eight of SMPN 3 Sungai Limau. The design of this research is descriptive research. The data were collected by using questionnaire and interviews. In this research, the researcher used total sample as a sampling technique for choosing the participants. The participants of this research consist of 79 students at grade eight from class VIII.1, VIII.2, and VIII.3 of SMPN 3 Sungai Limau. The result of this research find that the students have problems in linguistics problems and psychological problems. The linguistics problems consist of incorrect pronunciation with a percentage 88.61%, and followed by lack of vocabulary with, and mastering of grammar with same percentage 81.33%. The psychological linguistics consist of anxiety with a percentage 68.67%, mother tongue use with a percentage 72.15%, shyness with a percentage 70.25%, lack of confidence with a percentage 73.42%, and fear mistakes with a percentage 73.73%. The dominant problems face by the students in speaking English is linguistics problems with average 73.51%.